A scalable quorum-based location service in ad hoc and sensor networks. (19th February 2008) - Stojmenovic, Ivan; Liu, Dandan; Jia, Xiaohua
Location service provides position of mobile destination to source node so that position-based routing can be applied. Previous location service protocols suffer from partial flooding overhead, and/or location failure in group movement scenarios. To overcome those deficiencies, we propose a quorum-based location service. The basic idea is that destination node registers its location along a 'column' to form an update quorum. Source node makes a query along a 'row' to form a search quorum. The destination location is detected at the intersection between the update and search quorums. The overhead of each routing task, including location service, is O(√n), where n is the number of nodes in the network. Four strategies are proposed to adjust the quorum system and improve it's performance. To guarantee the success of location retrieval, both search and update quorums are extended by face routing which traverses outer boundary of the network. The simulation results show that our proposed location service has high success rate and good scalability.